REALIZATION OF JOKOWI’S HIDDEN IDEOLOGY IN THE STATE SPEECH TEXT: A TRANSITIVITY ANALYSIS - Siti Noor Fazelah Mohd Noor; Suswanto Iswandi Megah S (PARADIGM: Journal of Language and Literary Studies, 2020)
This paper deals with the representation of the Indonesian people in Jokowi's statespeech texts. This paper employed Transitivity Analysis (M. A. K. Halliday Matthiessen, 2014) and socio semiotic theory (Leeuwen, 2008). Those were framedto analyze the clauses based on the state speech of Jokowi. This paper was retrievedfrom the full-speech text, which was on Setkab.go.id (Secretary of cabinets). Thispaper found that the people are the highest frequency (55 occurrences or 49,1 %),then the government comes to the second position with (43 occurrences or 38 %),afterward the President with (10 occurrences or 8,9 %). The least occurrence comesto the politician with (4 occurrences or 3,6 %). The People is represented the mostoccurrences indicates Jokowi represents the people of Indonesia as the acting taker.On the other hand, the politician is the least occurrences represented by Jokowishows how he tends to avoid conflict with the politicians. The paper concluded thatJokowi has an ideological stance to prioritize the people as the acting taker that thepeople is activated actor. It shows that Jokowi's ideological realization is an actingtaker in his state speech.